2022
DOI: 10.24875/bmhim.21000077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and functional outcome of pediatric ocular trauma in a third level reference hospital in Guadalajara, Mexico

Abstract: Background: Ocular trauma is one of the leading causes of decreased visual acuity and monocular blindness in the pediatric population. Since its occurrence is potentially preventable, it is essential to understand its demographic characteristics and risk factors to alert and implement prevention and health promotion programs. Methods: We conducted a retrospective study in which we reviewed 187 clinical records of patients ≤ 15 years old with the diagnosis of severe ocular trauma admitted in 2017 to the Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Next in line of frequency were those in the closed globe trauma category, including hyphema and cataracts. In addition, when compared with similar studies, we found conflicting remarks because several studies 1,4,10,23,24,26,28,39 had open globe trauma as the most common outcome from the insult, whereas several others 7,11,19,22,27,29,34,35 reported closed globe trauma to be the case, the most common manifestation of which was hyphema, subconjunctival hemorrhage, and ocular/adnexa contusion.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Next in line of frequency were those in the closed globe trauma category, including hyphema and cataracts. In addition, when compared with similar studies, we found conflicting remarks because several studies 1,4,10,23,24,26,28,39 had open globe trauma as the most common outcome from the insult, whereas several others 7,11,19,22,27,29,34,35 reported closed globe trauma to be the case, the most common manifestation of which was hyphema, subconjunctival hemorrhage, and ocular/adnexa contusion.…”
Section: Discussionmentioning
confidence: 79%
“…[16][17][18] Moreover, although the prevalence is decreasing, many defects require immediate surgical intervention, leaving the affected individual's caretakers with heavy financial burdens. 4,19,20 Therefore, identifying the type of mechanisms of harm, their prevalence, and ways to improve the methods of surveillance and supervision to control the incidences is of extreme value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations